Effectiveness of Menstrual Calender Application to Adolescent Girl Behavior in District Gunung Anyar Tambak City of Surabaya - Desta Ayu Cahya Rosyida (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
Out of wedlock pregnancy is an example of the lack of understanding, knowledge, attitudes and behavior regarding reproductive health. One effort to increase understanding is by introducing many ways about reproductive health, one of which is by introducing the way to know the menstrual cycle. Technological sophistication actually makes it easie for everyone to obtain information via the internet. Then anyone can actually use the application on the mobile. So the every teen can know the menstrual cycle well and know how long the menstrual cycle. The aims is Application Menstrual Calender for young women to know the regular menstrual cycle or not. It was a quantitative study using Quasi Experiment with one group comparation pretest-posttest design. A sample of 34 young women aged 10-22 years and using a total sampling technique.In this design the treatment is carried out, then the conditions before and after the treatment are compared. Wilcoxon Signed Ranks Test showed that Menstrual. The average age of respondents is 17 years included in the category of late teens (66.7%) and the average education of respondents who actively use the menstrual calendar application that is high school (100%). Adolescent girls behavior behaves positively (61, 8%). Calendar application was effective on adolescent girls' behavior.